Is Bobcatsss Preparing its Participants for Digital Transformation? Topic Analysis of Papers Presented at Bobcatsss Conferences from 2015 to 2020 - Golub, Antonija; Pjanić, Valentina; Ćošić, Tina; Cupar, Drahomira (Bobcatsss, 2023)
This paper deals with a topic analysis of papers presented at the BOBCATSSS conferences from 2015 to 2020. The corpus for this research was gathered from conference proceedings and includes only paper presentations and excludes posters, workshops, pecha-kucha, etc. Sample consists of 234 collected papers. Content analysis was done by using a classification scheme for library & information sciences compiled by Järvelin and Vakkari (1990), and developed further by Tuomaala, Jarvelin, Vakkari (2014). Content analysis, i.e. indexing was applied only on titles, and was done by all authors individually. After the indexing of all 234 titles, results were gathered in topical clusters, created using a proposed classification scheme. The aim of the paper is to explore the distribution of the topics presented at the BOBCATSSS conference and compare them against the topics gathered around this years’ main theme: digital transformation. This analysis will explore in more details all papers found dealing with digital content, digitalization, information and communication technology, etc. Research questions are as followed: 1. Which areas are most represented within the papers presented at the BOBCATSSS conferences from 2015 till 2020? 2. How are topics in the area of digital transformation represented in BOBCATSSS conferences from 2015 till 2020? 3. Is BOBCATSSS following trends in relevant topics in the field of library & information sciences?